1992
DOI: 10.1111/j.1365-2621.1992.tb01195.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified atmospheres on textural and cell wall changes of asparagus during shelf‐life

Abstract: Spears of asparagus cultivator (cv) Regal harvested from a commercial crop on 16 May, 30 May, and 6 June, 1989 were packaged in rigid PVC trays (300g per pack) over-wrapped with non-perforated 15 p stretch PVC (Auto RMF-A), a similar micro-perforated film or with a highly perforated control film. Packs were held at 8°C for 1 d, then transferred to 20°C to simulate commercial cool chain distribution and ambient display. Respiration rates as mg C 0 2 production kg-' h-' were determined for each harvest, and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
4

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 18 publications
0
8
0
4
Order By: Relevance
“…The change in texture of asparagus has been related to fibrousness and can be attributed to lignification, but different studies have shown that other modifications of the cell wall composition could also be related to this alteration (Everson and others 1992; Rodríguez and others 2004; Albanese and others 2007). In our case, minimally processed asparagus underwent gradual softening during storage which made cutting more difficult and meant an increase in the effort necessary to complete it ( A 2 in Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The change in texture of asparagus has been related to fibrousness and can be attributed to lignification, but different studies have shown that other modifications of the cell wall composition could also be related to this alteration (Everson and others 1992; Rodríguez and others 2004; Albanese and others 2007). In our case, minimally processed asparagus underwent gradual softening during storage which made cutting more difficult and meant an increase in the effort necessary to complete it ( A 2 in Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…The speed with which changes occur in the attributes of color and texture in minimally processed asparagus is clearly affected by the conditions of storage and display. Several studies have concentrated on the influence of storage temperature on the shelf life of this product or packaging film permeability (Everson and others 1992; Siomos and others 2000). However, few studies have analyzed the influence that the unavoidable exposure to light during the time they are on sale has on the evolution of the quality parameters of this product (Nilsson 2000; Siomos and others 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The technology of MAP can extend the shelf-life of asparagus spears (Baxter & Waters, 1991;Everson, Waldron, Geeson, & Browne, 1992). Some researches showed that keeping green or white asparagus in non-perforated polyethylene bags at 1°C or polyethylene bags at 2°C, the shelf-life can reach 8-35 days (GarciaGimeno, Castillejo-Rodriguez, Barco-Alcala, & ZureraCosano, 1998;Lill, 1980;Osuna, Zurera, & Garcia, 1995).…”
Section: Introductionmentioning
confidence: 98%
“…The chemical basis of hardening is related to modifications of the cell wall composition and has traditionally been associated with lignification (Salunkhe and Desai 1984; Smith and Stanley 1987; Everson and others 1992). The presence of lignin is confined to vascular plants, where it is mainly deposited in cell walls of tissues involved in mechanical support or in water conduction such as xylem, sclerenchyma, phloem fibers, and periderm.…”
Section: Introductionmentioning
confidence: 99%